Evaluation of the biocompatibility of root canal sealers using subcutaneous implants - João E. Gomes-Filho; Brenda P. F. A. Gomes; Alexandre A. Zaia; Caio R. Ferraz; Francisco J. Souza-Filho (University of São Paulo, 2007)
The purpose of this study was to evaluate in vivo the biocompatibility of Endométhasone, Pulp Canal Sealer EWT and AH-Plus root canal sealers after implantation in rat connective tissue. Twenty-four Wistar-Furth rats were used. Polyethylene tubes were filled with the sealers and implanted into specific dorsal subdermal tissue sites of the rats. Implants were removed after 3, 7 and 30 days, fixed and processed for glycol methacrylate-embedding technique to be examined microscopically. On the 3rd day, there was a mild inflammatory reaction to Pulp Canal Sealer EWT implants, but a severe response to the other sealers with presence of acute inflammatory cells. On the 7th day, tissue organization was more evident with attenuation of the inflammatory reaction, especially for the AH-Plus implants. On the 30th day, connective tissue with few inflammatory cells was observed in contact with all sealer implants. In this time interval, the tissue in contact with Pulp Canal Sealer EWT implants was more organized, while the tissue close to Endométhasone and AH-Plus implants showed a mild persistent inflammatory reaction and had similar results to each other. In conclusion, the sealers had a similar pattern of irritation, which was more severe in the beginning and milder with time, in such a way that all sealers showed a persistent mild reaction. Pulp Canal Sealer EWT yielded better tissue organization than Endométhasone and AH-Plus, which, in turn, showed similar results to each other.